Teaching Higher Order Thinking Skills to Promote Islamic Junior High School Students’ Achievement in English Classroom - SETIA RINI; MANSUR MANSUR (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2019)
The research aimed at investigating (1) whether or not there was improvement on students’ achievement in English subject after the implementation of scientific approach and Higher Order Thinking Skills (HOTS,) and (2) what were the students’ perceptions towards the learning activities conducted at one of Islamic Junior High School in Salatiga consisting of 34 students. The study used Quantitative Method with Pre-Experimental approach by applying PretestPosttest design in order to see whether there was improvement or not prior to the implementation of the collaboration of scientific and higher order thinking skills (HOTS) and after the implementation of that teaching method. In order to gained the data of students’ English achievement, the test was administered to the students. Meanwhile, in order to see the students’ perception, the likert scale questionnaire items which comprised of 20 items was administered. The results showed that there was improvement on students’ achievement which was reflected from the significant improvement between the results of pretest and posttest. In other words, the profile of learning – teaching activities after practicing the collaboration of scientific and higher order thinking skills (HOTS) is improved. Furthermore, the results of questionnaire reflected that students had positive perceptions towards the learning activities.